Realisme Hukum: Peradilan Adat dalam Perspektif Keadilan Sosial - Rato, Dominikus (Jurnal Kajian Pembaruan Hukum, 2021)
Aspects of positivism with its normative approach are often taught in various law schools as a single perspective. The study of law can be based on legal realism. Nevertheless, there is still a debate about legal realism's working pattern and contribution to juridical science. This study that introduced legal realism worked with socio-legal method based on the literature review. It aimed to elaborate on the concept of legal-realism as an epistemology of the socio-legal school, which leads to the conception of customary law and legal anthropology. With a naturalistic approach and supported by theories of customary law and legal anthropology. This study showed that legal realism as a school in philosophy and juridical studies based on empirical studies need to be developed. It referred to legal realism conceptualized in Scandinavia and America that was suitable to Indonesia's legal context, especially customary law as the law that lives in society. Therefore, the law that lives in society is strengthened through verdict and law enforcement officers as symbols of the state. It suggested that legal realism is also taught in law schools at universities, so that legal academics have diverse points of view, both in the legal discipline and as a research method. KEYWORDS: Customary Law, Socio-Legal, Social Justice, Legal Realism.